# Ex.4.3 Q4 Simple-Equations Solutions-Ncert Maths Class 7

## Question

(a) Construct \(3\) equations starting with \(x = 2\)

(b) Construct \(3\) equations starting with \(x=-2\)

## Text Solution

**What is Known?**

Value of the variables; \(x = 2\) and \(x=-2\)

**What is unknown?**

\(3\) equations starting with \(x = 2\) and \(3\) equations starting with \(x = 2\)

**Reasoning:**

You can get the equation by adding, multiplying or subtracting the same value on both sides of the equation.

**Steps:**

(a) \(3\) equations starting with \(x = 2\)

**(i) **\(x = 2\)

Multiplying both sides by \(10\),

\(10x = 20\)

Adding \(2\) to both sides ,

\[\begin{align}10x + 2 &= 20 + 2\\10x + 2 &= 22\end{align}\]

**(ii)** \(x = 2\)

multiplying both sides by \(5\),

\(5x = 10\)

subtracting \(3\) to both sides,

\[\begin{align}5x - 3 &= 10 - 3\\5x - 3 &= 7\end{align}\]

**(iii) **\(x = 2\)

multiplying both sides by \(2\),

\(2x = 4\)

subtracting \(3\) to both sides,

\[\begin{align}2x - 3 &= 4 - 3\\2x - 3 &= 1\end{align}\]

(b) \(3\) equations starting with \(x = -2\)

**(i) **\(x=-2\)

Multiplying both sides by \(3\),

\(3x = - 6\)

**(ii) **\(x=-2\)

Multiplying both sides by \(3\),

\(3x = - 6\)

Adding \(7 \) to both sides we get.

\[\begin{align}3x + 7 &= - 6 + 7\\ 3x + 7 &= 1\end{align}\]

**(iii) **\(x=-2\)

Multiplying both sides by \(3\),

\(3x = - 6\)

Adding \(10\) to both sides, we get.

\[\begin{align}3x + 10 &= - 6 + 10\\ 3x + 10& = 4\end{align}\]